Lithium-carbon composite negative electrode material as well as preparation method and application thereof

By depositing nano -lithium in graphite pores and covering solid electrolytes, the problem of irreversible loss and electrical reduction of lithium -ion battery graphite negative materials during the first charging and cycle has been solved. stability.

CN119381416APending Publication Date: 2025-01-28LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310933227.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The graphite negative electrode material of the lithium-ion battery forms an irreversible SEI film during the first charging process, resulting in a decrease in charge and discharge efficiency. The deintercalation of lithium ions during the cycle process leads to the material powdering and deterioration of the conductivity, reducing the cycling performance of the battery.

Method used

Seven nano -lithium in graphite pores and cover solid electrolytes on the outer layer to improve the diffusion and conductivity of lithium ions and reduce volume expansion rates.

Benefits of technology

It improves the dehydration speed of lithium ion in the negative electrode material, enhances the large current charging and discharge performance, improves the ionic conductivity, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381416A_ABST
    Figure CN119381416A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a lithium-carbon composite negative electrode material as well as a preparation method and application thereof. The lithium-carbon composite negative electrode material comprises porous graphite serving as a carbon composite negative electrode material framework, nanoscale lithium metal deposited in pores of the porous graphite, and a solid electrolyte coating the outer layer of the porous graphite, the porosity of the porous graphite is 10%-60%, the pore size of the porous graphite is 1-700 nm, and the particle size of the porous graphite is 1-60 [mu] m; and the particle size of the nano lithium metal is 1 nm to 700 nm. By depositing nano lithium in graphite pores, the diffusion of the graphite negative electrode material to lithium ions is improved, the de-intercalation speed of the lithium ions in the negative electrode material is accelerated, and the high-current charge-discharge performance of the material is improved; and the outer layer is coated with the solid electrolyte, so that the ionic conductivity of the negative electrode graphite material is improved, and the volume expansion rate of the negative electrode graphite material after multiple deintercalation of lithium ions is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery negative electrode, and in particular to a lithium-carbon composite negative electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries play an important role in the current energy storage system due to their high specific energy, high battery voltage, stable discharge and multiple cycles, and are widely used in various electronic devices and electric vehicles. As an important component of lithium-ion batteries, negative electrode materials have also attracted the attention of many researchers.

[0003] As one of the negative electrode materials, graphite material has the following main problems after testing and market feedback: First, during the first charge process of lithium-ion batteries, a solid electrolyte interface (SEI) film is formed to protect the negative electrode surface, but the formation of SE I film will cause irreversible consumption loss of lithium ions, which increases the irreversible capacity of the first charge and discharge, and reduces the charge and discharge efficiency of the electrode material; Second, during the charge and discharge cycle of the battery, the continuous deintercalation of lithium ions often causes the volume expansion of the graphite material, resulting in the pulverization of the graphite material and separation from the current collector, which makes the negative electrode conductivity worse and reduces the cycle performance of the lithium-ion battery. At present, in the face of the above problems, doping and coating are still a mainstream means of treatment. After modification, the structure and surface state of the graphite negative electrode can be protected during the cycle process, enhancing the stability of the cycle. In addition, the introduction of metal and non-metal elements can also significantly improve the performance of negative electrode graphite. Summary of the invention

[0004] The purpose of the present invention is to provide a lithium-carbon composite negative electrode material and its preparation method and application. Nanolithium is deposited in the pores of graphite to improve the diffusion of lithium ions in the graphite negative electrode material, accelerate the deintercalation speed of lithium ions in the negative electrode material, and improve the high-current charge and discharge performance of the material; the outer layer is coated with a solid electrolyte to improve the ion conductivity of the negative electrode graphite material and reduce the volume expansion rate of the negative electrode graphite material after multiple deintercalation of lithium ions.

[0005] To this end, in a first aspect, an embodiment of the present invention provides a lithium-carbon composite negative electrode material, comprising: porous graphite as a skeleton of the carbon composite negative electrode material, nanoscale lithium metal deposited in the pores of the porous graphite, and a solid electrolyte coated on the outer layer of the porous graphite;

[0006] The porosity of the porous graphite is 10%-60%, the pore size is 1nm-700nm, the particle size of the porous graphite is 1um-60um; the particle size of the nano lithium metal is 1nm-700nm.

[0007] Preferably, the solid electrolyte comprises: one of a garnet-type solid electrolyte material, a NASICON-type solid electrolyte material, a LISICON-type solid electrolyte material, a perovskite-type solid electrolyte material and derivative materials thereof, and the particle size of the solid electrolyte is 30nm-500nm;

[0008] The graphite is one or more of natural graphite, artificial graphite and composite graphite.

[0009] Preferably, the mass of the nanoscale lithium metal deposited in the pores of the porous graphite accounts for 1%-15% of the mass of the porous graphite, and the mass of the outer-layer coated solid electrolyte accounts for 5%-30% of the total mass of the lithium-carbon composite negative electrode material.

[0010] In a second aspect, an embodiment of the present invention provides a method for preparing the lithium-carbon composite negative electrode material described in the first aspect, comprising:

[0011] The graphite material is placed in the heating zone of the reaction device, water is injected into the evaporation device, an inert gas is introduced into the reaction device, and the heating switch is turned on. The water in the evaporation device is evaporated into water vapor, and the water vapor is transported to the heating zone with the inert gas as a carrier to react with the graphite material at a set temperature in the heating zone to prepare a porous graphite material;

[0012] Placing lithium metal in a vapor deposition device, and controlling the vapor deposition temperature to be 300° C.-1400° C., and the lithium vapor flow rate to be 0.2 L / min-10 L / min; placing a porous graphite material in a deposition chamber of the vapor deposition device, evacuating the chamber, and passing lithium vapor into the deposition chamber, wherein the lithium vapor is adsorbed into the pores of the porous graphite material, cooled, and grown into nano lithium metal particles, thereby achieving the deposition of metallic lithium in the pores of the porous graphite, and obtaining a graphite material with lithium metal deposition;

[0013] The solid electrolyte material and the solvent are put into a mixer and mixed for 0.5h-5h to obtain a solid electrolyte slurry with a solid content of 5%-30%; then the lithium metal deposited graphite material and the solid electrolyte slurry are added to a ball mill according to a mass ratio of 0.02:1-0.3:1, mixed at 200rmp-600rmp for 1-6 hours, and dried in a vacuum oven for 2-24 hours. The obtained product is placed in a muffle furnace and heated to 300℃-1200℃ for calcination for 2-10 hours, so that the solid electrolyte slurry covers the porous graphite material, and the lithium-carbon composite negative electrode material is obtained.

[0014] Preferably, the reaction equipment is one or more of a multi-temperature zone tubular furnace, a vertical tubular furnace, a cylindrical tubular furnace, a vapor deposition furnace, and a box-type atmosphere furnace;

[0015] The inert gas is one or a combination of helium, nitrogen and argon.

[0016] Preferably, the set temperature of the heating zone of the reaction equipment is 700°C-1150°C;

[0017] The evaporation temperature of the evaporation equipment is 100°C-300°C;

[0018] The flow rate of the inert gas is 0.2L / min-10L / min;

[0019] The reaction time is 0.5h-10h.

[0020] Preferably, the solvent includes one or more of acetone, N,N-dimethylformamide, dimethyl carbonate, and ethylene carbonate.

[0021] In a third aspect, an embodiment of the present invention provides a lithium battery negative electrode, comprising the lithium-carbon composite negative electrode material described in the first aspect above.

[0022] In a fourth aspect, an embodiment of the present invention provides a lithium battery negative electrode, comprising a lithium-carbon composite negative electrode material prepared by the preparation method described in the second aspect above.

[0023] In a fifth aspect, an embodiment of the present invention provides a lithium battery, comprising the lithium battery negative electrode described in the third aspect or the fourth aspect.

[0024] The lithium-carbon composite negative electrode material provided in the embodiment of the present invention has deposited nano-metal lithium in the graphite pores, which can improve the diffusion of lithium ions in the graphite negative electrode material, accelerate the deintercalation speed of lithium ions in the negative electrode material, and improve the large current charge and discharge performance of the material; the outer layer is coated with a solid electrolyte, thereby improving the ionic conductivity of the negative electrode graphite material and reducing the volume expansion rate of the negative electrode graphite material after multiple deintercalation of lithium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 A flow chart of the method for preparing the lithium-carbon composite negative electrode material provided by the present invention;

[0026] Figure 2 This is a scanning electron microscope (SEM) image of the lithium-carbon composite negative electrode material provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0028] The embodiment of the present invention provides a lithium-carbon composite negative electrode material, comprising: porous graphite as a skeleton of the carbon composite negative electrode material, nano-scale lithium metal deposited in the pores of the porous graphite, and a solid electrolyte coated on the outer layer of the porous graphite;

[0029] The porosity of the porous graphite is 10%-60%, the pore size is 1nm-700nm, the particle size of the porous graphite is 1um-60um; the particle size of the nano lithium metal is 1nm-700nm.

[0030] The mass of the nano-scale lithium metal deposited in the pores of the porous graphite accounts for 1%-15% of the mass of the porous graphite, and the mass of the solid electrolyte coated on the outer layer accounts for 5%-30% of the total mass of the lithium-carbon composite negative electrode material. The solid electrolyte used in the present invention includes: one of garnet-type solid electrolyte material, NASICON-type solid electrolyte material, LISICON solid electrolyte material, perovskite-type solid electrolyte material and their derivative materials, and the particle size of the solid electrolyte is 30nm-500nm; the graphite is selected from one or more of natural graphite, artificial graphite, and composite graphite.

[0031] In the above technical solution, porosity refers to the percentage of pore space in the material to the total volume. In the design of the present invention, the porosity of porous graphite is 10%-60%. A moderate porosity can provide sufficient space so that nano-scale lithium metal can be fully deposited in the pores of porous graphite. This helps to increase the contact area between the electrode and lithium ions, thereby improving the capacity and charge and discharge rate of the electrode. The pore size refers to the size of the pore. In the design of the present invention, the pore size is 1nm-700nm. Smaller pore sizes can provide more surface area, which is conducive to the deposition of nano-scale lithium metal and the diffusion of lithium ions in the pore structure, thereby improving the reaction rate and power performance of the electrode. The particle size of porous graphite refers to the size of the material particles. The particle size of porous graphite designed by the present invention is 1um-60um. This helps to provide a larger specific surface area, enhance the interaction between the material and lithium ions, and improve the conductivity and lithium insertion performance of the material. The particle size of nano lithium metal is designed to be 1nm-700nm, which can fully fill the porous graphite and is beneficial to increase the insertion / deinsertion speed of lithium. Because the smaller particle size has a higher surface energy, it is easier to adsorb and diffuse lithium ions, thereby improving the battery's charge and discharge rate and cycle stability.

[0032] The outer layer of solid electrolyte is designed to improve the ionic conductivity of the negative electrode graphite material and reduce the volume expansion rate of the negative electrode graphite material after multiple lithium ion insertion and extraction. The solid electrolyte has good ion conductivity and stability, can effectively inhibit the volume change of the material, slow down the aging process of the material, thereby improving the cycle life and safety of the battery.

[0033] In summary, through the design of the negative electrode material structure and composition of the present invention, the lithium-carbon composite negative electrode material can obtain better charge and discharge performance, cycle stability and safety, so that it can be used as a negative electrode material in energy storage devices such as lithium-ion batteries, and has good application prospects.

[0034] The above-mentioned lithium carbon composite negative electrode material can be obtained by Figure 1 The method steps shown are used to prepare the Figure 1 The preparation method of the lithium-carbon composite negative electrode material of the present invention mainly includes:

[0035] Step 110, placing a graphite material in a heating zone of a reaction device, injecting water into an evaporation device, introducing an inert gas into the reaction device, turning on a heating switch, evaporating the water in the evaporation device into water vapor, and transporting the water vapor to the heating zone using the inert gas as a carrier to react with the graphite material at a set temperature in the heating zone, thereby preparing a porous graphite material;

[0036] The reaction equipment in this step is one or more of a multi-temperature zone tubular furnace, a vertical tubular furnace, a cylindrical tubular furnace, a vapor deposition furnace, and a box-type atmosphere furnace;

[0037] The inert gas is one or a combination of helium, nitrogen and argon.

[0038] The set temperature of the heating zone of the reaction equipment is 700°C-1150°C; the evaporation temperature of the evaporation equipment is 100°C-300°C; the flow rate of the inert gas is 0.2L / min-10L / min; and the reaction time for preparing the porous graphite material is 0.5h-10h.

[0039] Step 120, placing lithium metal in an evaporation device, and controlling the evaporation temperature to be 300° C.-1400° C., and the lithium vapor flow rate to be 0.2 L / min-10 L / min; placing a porous graphite material in a deposition chamber of a vapor deposition device, evacuating the chamber, and passing lithium vapor into the deposition chamber, wherein the lithium vapor is adsorbed into the pores of the porous graphite material, cooled, and grown into nano lithium metal particles, thereby achieving the deposition of metallic lithium in the pores of the porous graphite, and obtaining a graphite material with lithium metal deposition;

[0040] Step 130, putting the solid electrolyte material and the solvent into a mixer and mixing for 0.5h-5h to obtain a solid electrolyte slurry with a solid content of 5%-30%; then adding the lithium metal deposited graphite material and the solid electrolyte slurry into a ball mill according to a mass ratio of 0.02:1-0.3:1, mixing at 200rmp-600rmp for 1-6 hours, and drying in a vacuum oven for 2-24 hours, placing the obtained product in a muffle furnace and heating it to 300°C-1200°C for calcination for 2-10 hours, so that the solid electrolyte slurry covers the porous graphite material, that is, the lithium-carbon composite negative electrode material is obtained.

[0041] The solvent includes one or more of acetone, N,N-dimethylformamide, dimethyl carbonate, and ethylene carbonate.

[0042] The lithium-carbon composite negative electrode material prepared by the above method can be used as a lithium battery negative electrode in lithium-ion batteries.

[0043] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0044] Example 1

[0045] 1) Weighing 100 g of natural graphite and placing it in the heating zone of a multi-temperature zone tubular furnace, placing water in an evaporation device, heating it to 100° C. to evaporate it into water vapor, and then using argon as a carrier to transport the water vapor to the heating zone of the tubular furnace to react with the natural graphite at 1000° C. for 5 hours to obtain a porous graphite material;

[0046] 2) placing lithium metal in an evaporation device, controlling the evaporation temperature to 800° C. and the lithium vapor flow rate to 1 L / min; placing the porous graphite material obtained in 1) in a deposition chamber of a vapor deposition device, and then introducing lithium vapor into the deposition chamber, wherein the lithium vapor is adsorbed into the pores of the porous graphite, and then cooled and grown into nano lithium metal particles, thereby obtaining a graphite material with lithium metal deposition.

[0047] 3) Weigh 20g of NASICON solid electrolyte lithium aluminum titanium phosphate (LATP) solid electrolyte powder, then add 80g of acetone and put it into a mixer and mix for 5h to obtain a LATP slurry with a solid content of 20%; then take 100g of the lithium metal deposited graphite material obtained in 2) and 5g of the above LATP slurry according to a mass ratio of 0.05:1 and add them to a ball mill, mix at 500rmp for 6 hours, and after drying in a vacuum oven for 12 hours, place the resulting product in a muffle furnace and heat it to 1000°C and calcine for 6 hours to obtain a lithium-carbon composite negative electrode material.

[0048] Figure 2 This is a scanning electron microscope image of the lithium-carbon composite negative electrode material provided in Example 1 of the present invention. According to the scanning electron microscope measurement, the pore size of the porous graphite in this embodiment is 200nm-300nm, the particle size of the porous graphite is 10um-20um, the particle size of the nano lithium metal is 40nm-50nm, and the particle size of the solid electrolyte is 60nm-100nm. The porosity is calculated by the mass volume method, and the calculated porosity of the porous graphite is about 24%.

[0049] Example 2

[0050] 1) Weighing 100 g of natural graphite and placing it in the heating zone of a multi-temperature zone tubular furnace, placing water in an evaporation device, heating it to 100° C. to evaporate it into water vapor, and then using argon as a carrier to transport the water vapor to the heating zone of the tubular furnace to react with graphite at 1000° C. for 5 hours to obtain a porous graphite material;

[0051] 2) placing lithium metal in an evaporation device, controlling the evaporation temperature to 800° C. and the lithium vapor flow rate to 0.5 L / min; placing the porous graphite obtained in 1) in a deposition chamber of a vapor deposition device, and then introducing lithium vapor into the deposition chamber, wherein the lithium vapor is adsorbed into the pores of the porous graphite, and then cooled and grown into nano lithium metal particles, thereby obtaining a graphite material with lithium metal deposition.

[0052] 3) Weigh 20g of garnet-type solid electrolyte lithium lanthanum zirconium tantalum oxide (LLZTO) solid electrolyte powder, then add 80g of acetone and put it into a mixer and mix for 5h to obtain a LLZTO slurry with a solid content of 20%; then take 100g of the lithium metal-deposited graphite material in 2) and 5g of the above LLZTO slurry according to a mass ratio of 0.05:1 and add them to a ball mill, mix at 500rmp for 6 hours, and after drying in a vacuum oven for 12 hours, place the resulting product in a muffle furnace and heat it to 1000°C and calcine for 6 hours to obtain a lithium-carbon composite negative electrode material.

[0053] Example 3

[0054] 1) Weighing 100 g of natural graphite and placing it in the heating zone of a multi-temperature zone tubular furnace, placing water in an evaporation device, heating it to 100° C. to evaporate it into water vapor, and then using argon as a carrier to transport the water vapor to the heating zone of the tubular furnace to react with graphite at 1000° C. for 5 hours to obtain a porous graphite material;

[0055] 2) placing lithium metal in an evaporation device, controlling the evaporation temperature to 800° C. and the lithium vapor flow rate to 0.5 L / min; placing the porous graphite obtained in 1) in a deposition chamber of a vapor deposition device, and then introducing lithium vapor into the deposition chamber, wherein the lithium vapor is adsorbed into the pores of the porous graphite, and then cooled and grown into nano lithium metal particles, thereby obtaining a graphite material with lithium metal deposition.

[0056] 3) Weigh 20g of perovskite-type solid electrolyte lithium lanthanum titanium oxide (LLTO) solid electrolyte powder, then add 80g of acetone and put it into a mixer and mix for 5h to obtain a LATP slurry with a solid content of 20%; then take 100g of the lithium metal-deposited graphite material obtained in 2) and 10g of the above-mentioned LLTO slurry according to a mass ratio of 0.1:1, add them to a ball mill, mix at 500rmp for 6 hours, and after drying in a vacuum oven for 12 hours, place the resulting product in a muffle furnace and heat it to 1000°C and calcine for 6 hours to obtain a lithium-carbon composite negative electrode material.

[0057] Example 4

[0058] 1) Weighing 100 g of artificial graphite and placing it in the heating zone of a multi-temperature zone tubular furnace, placing water in an evaporation device, heating it to 100° C. to evaporate it into water vapor, and then using argon as a carrier to transport the water vapor to the heating zone of the tubular furnace to react with graphite at 1000° C. for 5 hours to obtain a porous graphite material;

[0059] 2) placing lithium metal in an evaporation device, controlling the evaporation temperature to 800° C. and the lithium vapor flow rate to 0.5 L / min; placing the porous graphite obtained in 1) in a deposition chamber of a vapor deposition device, and then introducing lithium vapor into the deposition chamber, wherein the lithium vapor is adsorbed into the pores of the porous graphite, and then cooled and grown into nano lithium metal particles, thereby obtaining a graphite material with lithium metal deposition.

[0060] 3) Weigh 20g of NASICON solid electrolyte lithium aluminum titanium phosphate (LATP) solid electrolyte powder, then add 80g of acetone and put it into a mixer and mix for 5h to obtain a LATP slurry with a solid content of 20%; then take 100g of the lithium metal deposited graphite material obtained in 2) and 20g of the above LATP slurry according to a mass ratio of 0.2:1 and add them to a ball mill, mix at 500rmp for 6 hours, and after drying in a vacuum oven for 12 hours, place the resulting product in a muffle furnace and heat it to 1000°C and calcine for 6 hours to obtain a lithium-carbon composite negative electrode material.

[0061] Comparative Example 1

[0062] The negative electrode material provided in this comparative example is a graphite material, specifically the natural graphite used in Example 1.

[0063] Comparative Example 2

[0064] The negative electrode material provided in this comparative example is a porous graphite material, specifically the porous graphite material prepared in 1) of Example 1.

[0065] Comparative Example 3

[0066] The negative electrode material provided in this comparative example is a lithium metal deposited graphite material, specifically the lithium metal deposited graphite material prepared in 2) of Example 1.

[0067] To better illustrate the effects of the embodiments of the present invention, the following provides performance tests of graphite half-cells of the embodiments and comparative examples. Graphite half-cells of Embodiments 1, 2, 3, 4 and Comparative Examples 1, 2, 3 were prepared under the same conditions to perform rate performance and cycle performance tests.

[0068] The graphite half-cell consists of: a current collector of copper foil, a positive electrode of lithium-carbon composite material, a negative electrode of lithium metal, a polyethylene (PE) separator, and an electrolyte of 1 mol / L LiPF6 @Ethylene carbonate (EC) + dimethyl carbonate (DMC) (V:V = 1:1) electrolyte. The assembled button half-cell was left for 8 hours and then tested with the Blue Battery Test System. The button half-cell was subjected to constant current charge and discharge tests at different rates and long cycle tests at 1C rate within the voltage range of 0.01-1.5V at 25℃. The test data are shown in Tables 1 and 2.

[0069] Table 1 shows the test data of discharge specific capacity at different rates.

[0070]

[0071] Table 1

[0072] By analyzing the above experimental data, it can be seen that in terms of rate performance, the lithium-carbon composite negative electrode used in the present invention can effectively improve the cycle performance of the graphite half-cell, especially improve the large current charge and discharge performance of the material.

[0073] Table 2 shows the cycle capacity retention rate test data.

[0074] 100 cycles capacity retention rate 200 cycles capacity retention rate 500 cycles capacity retention rate Example 1 >95% >95% >90% Example 2 >95% >90% >80% Example 3 >95% >90% >80% Example 4 >95% >90% >80% Comparative Example 1 >85% >70% >50% Comparative Example 2 >90% >80% >60% Comparative Example 3 >90% >85% >70%

[0075] Table 2

[0076] By analyzing the above experimental data, it can be seen that in terms of cycle performance, the lithium-carbon composite negative electrode used in the present invention can effectively improve the cycle performance of the graphite half-cell and extend the service life of the battery.

[0077] The lithium-carbon composite negative electrode material and the corresponding preparation method provided in the embodiment of the present invention improve the diffusion of lithium ions in the graphite negative electrode material by depositing nano-lithium in the pores of graphite, accelerate the deintercalation speed of lithium ions in the negative electrode material, and improve the large current charge and discharge performance of the material; at the same time, the outer layer adopts a coated solid electrolyte to improve the ionic conductivity of the negative electrode graphite material and reduce the volume expansion rate of the negative electrode graphite material after multiple deintercalation of lithium ions.

[0078] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A lithium-carbon composite negative electrode material, characterized in that: The lithium-carbon composite negative electrode material comprises: porous graphite as a skeleton of the carbon composite negative electrode material, nano-scale lithium metal deposited in the pores of the porous graphite, and a solid electrolyte coated on the outer layer of the porous graphite; The porosity of the porous graphite is 10%-60%, the pore size is 1nm-700nm, the particle size of the porous graphite is 1um-60um; the particle size of the nano lithium metal is 1nm-700nm.

2. The lithium-carbon composite negative electrode material according to claim 1, characterized in that: The solid electrolyte comprises: one of a garnet-type solid electrolyte material, a NASICON-type solid electrolyte material, a LISICON-type solid electrolyte material, a perovskite-type solid electrolyte material and derivative materials thereof, and the particle size of the solid electrolyte is 30nm-500nm; The graphite is one or more of natural graphite, artificial graphite and composite graphite.

3. The lithium-carbon composite negative electrode material according to claim 1, characterized in that: The mass of the nano-scale lithium metal deposited in the pores of the porous graphite accounts for 1%-15% of the mass of the porous graphite, and the mass of the outer-layer coated solid electrolyte accounts for 5%-30% of the total mass of the lithium-carbon composite negative electrode material.

4. A method for preparing the lithium-carbon composite negative electrode material according to claim 1, characterized in that: The preparation method comprises: The graphite material is placed in the heating zone of the reaction device, water is injected into the evaporation device, an inert gas is introduced into the reaction device, and the heating switch is turned on. The water in the evaporation device is evaporated into water vapor, and the water vapor is transported to the heating zone with the inert gas as a carrier to react with the graphite material at a set temperature in the heating zone to prepare a porous graphite material; Placing lithium metal in a vapor deposition device, and controlling the vapor deposition temperature to be 300° C.-1400° C., and the lithium vapor flow rate to be 0.2 L / min-10 L / min; placing a porous graphite material in a deposition chamber of the vapor deposition device, evacuating the chamber, and passing lithium vapor into the deposition chamber, wherein the lithium vapor is adsorbed into the pores of the porous graphite material, cooled, and grown into nano lithium metal particles, thereby achieving the deposition of metallic lithium in the pores of the porous graphite, and obtaining a graphite material with lithium metal deposition; The solid electrolyte material and the solvent are put into a mixer and mixed for 0.5h-5h to obtain a solid electrolyte slurry with a solid content of 5%-30%; then the lithium metal deposited graphite material and the solid electrolyte slurry are added to a ball mill according to a mass ratio of 0.02:1-0.3:1, mixed at 200rmp-600rmp for 1-6 hours, and dried in a vacuum oven for 2-24 hours. The obtained product is placed in a muffle furnace and heated to 300℃-1200℃ for calcination for 2-10 hours, so that the solid electrolyte slurry covers the porous graphite material, and the lithium-carbon composite negative electrode material is obtained.

5. The preparation method according to claim 4, characterized in that: The reaction equipment is one or more of a multi-temperature zone tubular furnace, a vertical tubular furnace, a cylindrical tubular furnace, a vapor deposition furnace, and a box-type atmosphere furnace; The inert gas is one or a combination of helium, nitrogen and argon.

6. The preparation method according to claim 4, characterized in that: The set temperature of the heating zone of the reaction equipment is 700°C-1150°C; The evaporation temperature of the evaporation equipment is 100°C-300°C; The flow rate of the inert gas is 0.2L / min-10L / min; The reaction time is 0.5h-10h.

7. The preparation method according to claim 4, characterized in that: The solvent includes one or more of acetone, N,N-dimethylformamide, dimethyl carbonate, and ethylene carbonate.

8. A lithium battery negative electrode, characterized in that: The negative electrode comprises the lithium-carbon composite negative electrode material according to any one of claims 1 to 3.

9. A lithium battery negative electrode, characterized in that: The negative electrode comprises a lithium-carbon composite negative electrode material prepared by the preparation method described in any one of claims 4 to 7.

10. A lithium battery, characterized in that: The lithium battery comprises the lithium battery negative electrode as described in claim 8 or 9 above.